Material Teach Differentiated Style Study for Increase Mathematical Problem Solving Abilities - Pipin Sumarni; Yerizon; Erni Suharti; Anny Sovia (Rangkiang Mathematics Journal, 2023)
This research was carried out with the aim of finding out the problems found in tenth grade, or what is called Phase E. This research is expected to be able to overcome the problems of students who experience problems in solving problems by looking at students' learning styles. The type of research used in this research is a classroom action research method with a qualitative approach. The instruments used in this research were a learning style questionnaire, observation sheets to observe interactions between teachers and students, as well as interactions between students during the mathematics learning process. This research was conducted in phase E. From the research conducted, it was found that the use of teaching materials with differentiated learning styles can improve students' problem-solving abilities. It can be seen because there is an increase from the initial diagnostic student scores to the second cycle.